Proposal for an open telemetric system for sequential observational analysis in physical education and sport - Zabala, M.; Viciana, J.; Requena, B.; Lozano, L. (International Journal of Computer Science in Sport, 2002)
It is commonly accepted that visual feedback (FB) improves sport skill acquisition (Horn et al., 2002). In order to improve sport technique, it has been shown that visual FB of an execution can be processed on a later stage improving the precision in the following executions without visual FB (Hodges and Franks, 2002; Khan et al., 2002). In the same way, the efficacy in the applicability of visual FB has been proved to improve tactics in team sports (Morya et al., 2003; Viciana et al. 2002; Yen and Radwin 1995; Eon and Schütz, 1992).